Technogenic Disturbance of Soils under the Influence of Industrial Enterprises - Jo`rayevna, Ro`ziyeva Inobat; Bahramovna, Raupova Nodira (American Journal of Biology and Natural Sciences, 2025)
Due to the population growth and high demand for products in the Tashkent region, the spread of various chemical elements from industry, manufacturing, mining and factories currently leads to soil pollution in the regions. The role of industrial sectors in technogenic pollution in changing the ecological state of the regional ecosystem under the influence of individual industrial sectors located in three districts of the Tashkent region, namely Akhangaron district, Bekabad city and Almalyk city, is analyzed. Dark gray and typical sierozems, brown, gray-meadow, typical and light sierozems, meadow-gray, meadow and marsh-meadow soils are widespread in the region.